Contexts and conditions for a level playing field: Elite athletes` perspectives on anti-doping in practice - Efverström, A.; Bäckström, Å.; Ahmadi, N.; Hoff, D. (Performance Enhancement & Health, 2016)
The implementation of global anti-doping regulations was intended to provide a level playing field for all athletes entering sports competitions. However, studies have shown that the worldwide harmonization of rules has not been entirely efficacious. For instance, great variation has been found in how anti-doping organizations implement anti-doping regulations, and it has also been shown that athletes distrust the equivalence of the worldwide rules as regards their effects. The purpose of the present article is to examine how elite athletes from different contexts experience anti-doping procedures and to analyse the legitimacy of anti-doping practice. In order to capture a variety of voices and perspectives, 13 elite athletes from five different continents and three international sports federations were interviewed. The analysis shows that when global anti-doping policy is implemented in different contexts and under different conditions, inequities and structural injustices emerge concerning infrastructure, knowledge and support at the individual athlete level. These consequences may have implications for the legitimacy of anti-doping work, because the existence of procedural justice may be called into question. We therefore suggest that anti-doping policy-making should be based on taking into account these different conditions and being aware of the perspectives that underpin regulations intended to be applied global.